Action simulation in hallucination-prone adolescents - Dahoun, Tarik; Eliez, Stephan; Chen, Fei; Badoud, Deborah; Schneider, Maude; Larøi, Frank; Debbané, Martin (Frontiers in Human Neuroscience, 2013)
Theoretical and empirical accounts suggest that impairments in self-other discrimination processes are likely to promote the expression of hallucinations. However, our understanding of such processes during adolescence is still at an early stage. The present study thus aims 1) to delineate the neural correlates sustaining mental simulation of actions involving self-performed actions (first-person perspective; 1PP) and other-performed actions (third-person perspective; 3PP) during adolescence 2) to identify atypical activation patterns during 1PP/3PP mental simulation of actions in hallucination-prone adolescents 3) to examine whether differential risk for schizophrenia (clinical vs genetic) is also associated with differential impairments in the 1PP/3PP mental simulation of actions during adolescence. Twenty-two typically developing controls (Control group; 6 females), twelve hallucination-prone adolescents (AH group; 7 females) and thirteen adolescents with 22q11.2 Deletion Syndrome (22q11.2DS group; 4 females) were included in the study. During the fMRI task, subjects were presented with a cue (self-other priming cues) indicating to perform the task using either a first person perspective (“you”-1PP) or a third person perspective (“friend”-3PP) and then they were asked to mentally simulate actions based on the type of cue. Our results indicated that atypical patterns of cerebral activation, particularly in the key areas of self-other distinction, were found in both groups at risk for auditory hallucinations (AH and 22q11.2DS). More precisely, adolescents in the AH and 22q11.2DS groups presented decreased activations in the parieto-occipital region BA19 during 3PP. This study characterizes the neural correlates of mental imagery for actions during adolescence, and suggests that a differential risk for hallucination-proneness (clinical vs. genetic) is associated to similar patterns of atypical activations in key areas sustaining self-other discrimination processes.